2008
DOI: 10.1143/ptp.119.561
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Study of 9,10,11Li with the Tensor and Pairing Correlations

Abstract: We make a systematic study of Li isotopes (A = 9, 10, 11) in the tensor optimized shell model for 9 Li and treat the additional valence neutrons in the cluster model approach by taking into account the Pauli-blocking effect caused by the tensor and pairing correlations. We describe the tensor correlations in 9 Li fully in the tensor-optimized shell model, where the variation of the size parameters of the single particle orbits is essential for getting strong tensor correlations. We have shown in our previous s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 44 publications
2
68
3
Order By: Relevance
“…The existence of the virtual state is consistent with the dominant decay into 8 Be + n in the photodisintegration of 9 Be. The virtual state is often discussed in unstable nuclei, such as 10 Li and 11 Li [25,26,38]. For 10 Li, Masui et al [38] showed the explicit pole trajectory of the virtual state of 10 Li as a 9 Li + n picture, which is similar to the present 8 Be(0 + ) + n situation.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…The existence of the virtual state is consistent with the dominant decay into 8 Be + n in the photodisintegration of 9 Be. The virtual state is often discussed in unstable nuclei, such as 10 Li and 11 Li [25,26,38]. For 10 Li, Masui et al [38] showed the explicit pole trajectory of the virtual state of 10 Li as a 9 Li + n picture, which is similar to the present 8 Be(0 + ) + n situation.…”
Section: Resultsmentioning
confidence: 61%
“…Furthermore, the CSM has been developed to describe the breaking up of unstable nuclei. The CSM has been applied to the Coulomb breakup reactions of two-neutron halo nuclei into core + n + n scattering states and well reproduces the observed cross sections [24][25][26]. From the above, the CSM is promising means to discuss the excited states of 9 Be and the photodisintegration into unbound excited states of 9 Be on the same footing.…”
mentioning
confidence: 75%
“…In our previous study of 11 Li, we discuss those quantities of 11 Li in detail [25,26]. It is interesting to discuss the effect of the tensor force on these quantities in other Li isotopes using the TOSM+UCOM method.…”
Section: Discussionmentioning
confidence: 99%
“…Before the present analysis, for neutron-rich 10 Li and 11 Li, we have performed the coupled two-and three-body cluster model analyses assuming the 9 Li core described using the simplified TOSM wave function, respectively [6,25,26]. The cluster model for two nuclei precisely describes the neutron wave functions in a loosely bound state around 9 Li, such as a neutron halo structure in 11 Li.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30] A common prediction is that the valence halo neutrons exhibit a spatial correlation favoring the 'di-neutron' configuration with two neutrons coupled at small relative distances. The spatial correlation is also discussed in stable heavy nuclei with closed-shell core plus two neutrons, e.g.…”
Section: Cooper Pair In Neutron-rich Nucleimentioning
confidence: 99%